Transcriptomic and Metabolomic Profiling Reveals the Effect of LED Light Quality on Fruit Ripening and Anthocyanin Accumulation in Cabernet Sauvignon Grape - Zhang, Peian; Lu, Suwen; Liu, Zhongjie; Zheng, Ting; Dong, Tianyu; Jin, Huanchun; Jia, Haifeng; Fang, Jingggui (Frontiers in Nutrition, 2021)
Different light qualities have various impacts on the formation of fruit quality. The present study explored the influence of different visible light spectra (red, green, blue, and white) on the formation of quality traits and their metabolic pathways in grape berries. We found that blue light and red light had different effects on the berries. Compared with white light, blue light significantly increased the anthocyanins (malvidin-3-O-glucoside and peonidin-3-O-glucoside), volatile substances (alcohols and phenols), and soluble sugars (glucose and fructose), reduced the organic acids (citric acid and malic acid), whereas red light achieved the opposite effect. Transcriptomics and metabolomics analyses revealed that 2707, 2547, 2145, and 2583 differentially expressed genes (DEGs) and (221, 19), (254, 22), (189, 17), and (234, 80) significantly changed metabolites (SCMs) were filtered in the dark vs. blue light, green light, red light, and white light, respectively. According to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, most of the DEGs identified were involved in photosynthesis and biosynthesis of flavonoids and flavonols. Using weighted gene co-expression network analysis (WGCNA) of 23410 highly expressed genes, two modules significantly related to anthocyanins and soluble sugars were screened out. The anthocyanins accumulation is significantly associated with increased expression of transcription factors (VvHY5, VvMYB90, VvMYB86) and anthocyanin structural genes (VvC4H, Vv4CL, VvCHS3, VvCHI1, VvCHI2, VvDFR), while significantly negatively correlated with VvPIF4. VvISA1, VvISA2, VvAMY1, VvCWINV, VvβGLU12, and VvFK12 were all related to starch and sucrose metabolism. These findings help elucidate the characteristics of different light qualities on the formation of plant traits and can inform the use of supplemental light in the field and after harvest to improve the overall quality of fruit.